Systematic selections and forensic application evaluations of 111 individual identification SNPs in the Chinese Inner Mongolia Manchu group - Zhao, Congying; Xu, Hui; Fang, Yating; Zhao, Ming; Lan, Qiong; Chen, Man; Mei, Shuyan; Zhu, Bofeng (Frontiers in Genetics, 2022)
Single nucleotide polymorphism (SNP) possesses a promising application in forensic individual identification due to its wide distribution in the human genome and ability to do genotyping of degraded biological sample by designing short amplicons. Some commonly used individual identification SNPs are low polymorphic in East Asian populations. To improve the individual identification efficiencies in East Asian populations, SNP genetic markers with high polymorphisms were selected from the 1000 Genome Project III database in East Asian populations. A total of 111 SNPs with observed heterozygosity value greater than 0.4 were screened in East Asian populations, and then the forensic efficiencies of these selected SNPs were also evaluated in the Chinese Inner Mongolia Manchu group. The observed heterozygosity and power of discrimination values at 111 SNPs in the Inner Mongolia Manchu group ranged from 0.4011 to 0.7005, and 0.5620 to 0.8025, respectively, and the average value of polymorphism information content was greater than 0.3978. The cumulative match probability and combined probability of exclusion values at 111 SNPs were 7.447E-51 and 1-4.17E-12 in the Inner Mongolia Manchu group, respectively. The accumulative efficiency results indicated that these SNPs could be used as the potential tool for forensic individual identification and parentage testing in the Manchu group. The sequencing depths ranged from 781× to 12374×. The mean allele count ratio and noise level were 0.8672 and 0.0041, respectively. The sequencing results indicated that the SNP genetic marker detection based on the massively parallel sequencing technology has high sequencing performance and could meet the sequencing requirements of these SNPs in the studied group.